PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI ALGORITMA UNTUK KELAS X SMK MMENGGUNAKAN METODE ADDIE - Solihatunnisa, Astuti; Septiadi, Jaka (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study was motivated by the low level of student interest in learning algorithms at vocational high schools due to the lack of interactivity in the presentation of the material and the suboptimal integration of digital technology. Students tend to be more interested in digital-based learning with visualizations for abstract material; however, due to limitations in facilities, internet connectivity, and the availability of media, learning is still dominated by lectures and the use of PowerPoint. The study aims to develop interactive learning media for algorithm material for 10th-grade students at vocational high schools and to test the practicality and usability of the developed media. The Research & Development (R&D) method was used, employing the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 102 10th-grade students majoring in Software and Game Development (PPLG) and Automotive Engineering (TO) at SMKN 1 Sukatani. Data collection was conducted through interviews, a practicality questionnaire, and the System Usability Scale (SUS) questionnaire. The results of this study indicate that the developed media was rated as highly valid, with a 93.3% validity score by subject matter experts and an 86.6% score by media experts. The media’s practicality level averaged 85.2%, indicating it is highly practical, while the SUS score averaged 77.5, falling into the “good” category, meaning the media is easy to use and well-received by students. Based on the findings, the interactive learning materials developed are suitable for use and can help increase students' interest in learning.   Keywords: Interactive Learning Media; Algorithms; ADDIE model; Practicality; System Usability Scale.